2003
DOI: 10.1088/0268-1242/18/2/314
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence of diamond:Ce thin films

Abstract: We have observed light emission with a luminance of 3.5 cd m −2 from a diamond:Ce thin-film electroluminescence device at an applied voltage of 150 V. The electroluminescence spectrum at room temperature shows main peaks centred at 454 and 490 nm, which are attributed to isolated emission centres of Ce 3+ ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…The authors have cited additional references within the Supporting Information [22–27] . The supporting information includes results of photocatalysis experiments, effects of catalyst loading and pH value on the photocatalytic degradation of OTC‐HCl, Cyclic stability, Photoluminescence properties, synthetic process, Material Characterization and photocatalytic degradation of pollutants.…”
Section: Supporting Information Summarymentioning
confidence: 99%
“…The authors have cited additional references within the Supporting Information [22–27] . The supporting information includes results of photocatalysis experiments, effects of catalyst loading and pH value on the photocatalytic degradation of OTC‐HCl, Cyclic stability, Photoluminescence properties, synthetic process, Material Characterization and photocatalytic degradation of pollutants.…”
Section: Supporting Information Summarymentioning
confidence: 99%
“…As shown in Figure 4d, samples were irradiated with a monochromatic light (780 nm), and PL emission was observed due to the recombination of photogenerated charges. [50,51] The emission spectra showed that near band edge emission of FTO/CBO was reduced after Ag + -ions doping. Additionally, the emission of NACBO photoelectrode was further lowered when NiO-HSL was introduced at the back interface to extract the photogenerated holes.…”
Section: Optical Properties and Bandgap Calculationsmentioning
confidence: 99%
“…Self‐healing rubbers that intrinsically heal through chemical means such as the Diels–Alder mechanism, 3,4 disulphides exchange, 5–7 metal–ligand coordination, 8–10 hydrogen interaction, 11–13 as well as supramolecular ionic networks 14–16 have dominated self‐healing research until now 17,18 . Recently, incorporating the ionic interactions into epoxidized natural rubber (ENR) has shown to be an effective strategy for inducing self‐healing characteristics in the rubber material 12 .…”
Section: Introductionmentioning
confidence: 99%